Playing match venue does not affect resting salivary steroids in elite Futsal players - Arruda, A. F. S.; Aoki, M. S.; Miloski, B.; Freitas, C. G.; Moura, N. R.; Moreira, A. (Physiology & Behavior, 2016)
This study examined the influence of competition playing venue on the hormonal responses in elite Futsal players. Twenty-one males (age, 19.3 ± 0.7 years; height, 174.2 ± 4.1 cm; body mass, 71.8 ± 7.9 kg) from two Futsal teams were monitored during two competitive matches that were played against each other on a home and away basis. Saliva sampling was conducted before (pre) and after (post) each match. The concentration of salivary steroids (testosterone [T] and cortisol [C]) was assessed by ELISA. Resting concentration of salivary steroid (T and C) hormones was not affected by playing venue (home and away). Both Futsal matches promoted a significant increase in T and C from pre - to post-matches (p < 0.05), with a higher post-C concentration for playing at home (p < 0.05). No effect of playing venue on T was observed. In conclusion, the findings of this study indicate that the playing venue did not elicit a significant change in resting concentration of salivary steroid hormones. However, playing home induced a greater post-match C response, suggesting that the pressure for positive results in front of supporters, families and friends may impose a higher level of stress on the players at their own facility.